ANALISIS LIKUIDITAS SAHAM PADA PERUSAHAAN YANG MELAKUKAN STOCK SPLIT: PENGUJIAN TERHADAP TRADING RANGE THEORY PADA BURSA EFEK INDONESIA (Studi Pada Perusahaan Yang Melakukan Stock Split Tahun 2017-2019) - Tanjung, Abdul Hafiz; Ali, Sihabudin (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
This study aims to determine whether there is empirical evidence of stock split events in accordance with trading range theory or not. The empirical study was conducted on 28 samples of spliting firm and 86 samples of non spliting firm in Indonesia Stock Exchange from 2017 to 2019. The sampling technique used is random sampling. The method used is independent t test and paired samples t test. The result of this research show there is trading range on market stock price in year 2017, 2018, and 2019; and also shown by trading volume stock.